The learning performance of indigenous students in Nepali private schools: a mixed-methods study - Khadka, J; Adhikari, KP; Dahal, N (Eskişehir Osmangazi University, 2022)
One of the primary goals of schools is to improve the students' learning performance. Considering the factors associated to students' indigeneity contributing to their learning performances, this study explored the learning performances of ‘indigenous’ (Janajati) students in Nepali private secondary schools. Grounded in Bourdieu's (1986) cultural capital theory, the investigation employed a two-staged mixed-methods research process. In the first phase, longitudinal data (grade XII exam results) of 770 students between 2015 and 2019 at a case study school in Kathmandu were obtained and analysed. The quantitative results yielded from the descriptive analyses revealed that Janajati students, namely the Tamang, Magar, Gurung, Rai, and Limbu students included in the study, had a lower academic performance as compared to their non-Janajati counterparts. These results are consonant with overall national patterns in Nepal. In an attempt to explain these differences, a sequential qualitative study was undertaken through indepth interviews with five participants (three students and two teachers affiliated to the case study school from the same indigenous groups). For analytical purposes, factors influencing students’ performance were grouped into home-related and school-related themes. The study showed that home-related factors were more prevalent than the school-related factors in the students with lower learning performances. While family economic backgrounds and parental education also had a role to play, cultural factors (such as relative lack of predisposition towards education and aspiration for different occupations) were the most important factors influencing lower learning performance.